Essays on Foreign Exchange and Credit Risk - Andreas Bang Nielsen (Copenhagen Business School (CBS), 2018)
We investigate how currency denomination a ects the price of credit risky securities of the same issuer. We focus on eurozone sovereign quanto spreads, i.e., di erences in credit default swap (CDS) premiums denominated in U.S. dollar and Euro of the same reference entity. Quanto spreads of eurozone sovereigns reached unprecedented levels during the European debt crisis and have remained signi cant ever since. Quanto spreads do not simply re ect di erences in contractual terms linked to currency denomination, because CDS contracts trade under the same standardized terms independent of currency denomination, including credit events and recovery rates. In order to understand which factors drive quanto spreads, we propose a no-arbitrage model that shows in a simple and rigorous manner that quanto spreads arise without any market frictions through two risk channels. The rst channel, currency crash risk, re ects the risk of an adverse jump in domestic versus foreign currency triggered by default of the reference entity. Intuitively, currency crash risk causes the expected recovery payment to be relatively smaller on the domestic CDS compared to the foreign CDS, because the recovery payment on the domestic contract is received in the 'crashed' currency.
hdl:10398/9644
Keywords: 650